1996
DOI: 10.1136/adc.75.5.392
|View full text |Cite
|
Sign up to set email alerts
|

Parental and neonatal risk factors for atopy, airway hyper-responsiveness, and asthma.

Abstract: Background-Previous studies have not resolved the importance of several potential risk factors for the development of childhood atopy, airway hyperresponsiveness, and wheezing, which would allow the rational selection ofinterventions to reduce morbidity from asthma. Risk factors for these disorders were examined in a birth cohort of 1037 New Zealand children. Methods-Responses to questions on respiratory symptoms and measurements of lung function and airway responsiveness were obtained every two to three years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
116
6
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(138 citation statements)
references
References 45 publications
11
116
6
5
Order By: Relevance
“…5,7,8,26,30 Fergusson, in a New Zealand cohort study, found that the association between parental asthma and asthma in four-year-old children was true for boys but not girls, and concluded that the expression of asthma in genetically susceptible female children is delayed until middle childhood compared with its earlier expression in genetically susceptible boys. 8 The older age (7-9 years) of the children in our study may explain why we did not find such clear gender differences in the association between parental asthma and childhood asthma.…”
Section: Family Historymentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,8,26,30 Fergusson, in a New Zealand cohort study, found that the association between parental asthma and asthma in four-year-old children was true for boys but not girls, and concluded that the expression of asthma in genetically susceptible female children is delayed until middle childhood compared with its earlier expression in genetically susceptible boys. 8 The older age (7-9 years) of the children in our study may explain why we did not find such clear gender differences in the association between parental asthma and childhood asthma.…”
Section: Family Historymentioning
confidence: 99%
“…3,4 Prevalence studies in New Zealand 3,5,6 have identified various risk factors for childhood asthma, including male sex, 5,7 parental 3,5,6 or sibling asthma, 6 or having eczema during the first year of life. 6 However, there have also been inconsistent findings among these studies, including reports that paternal asthma 5 and parental eczema 6 are not significantly related to asthma in the child, and that the influence of parental asthma may depend on a child's gender. 8 More recently, a role for vaccination in promoting allergic sensitisation has been proposed.…”
mentioning
confidence: 99%
“…Common manifestations of allergic disease include allergic rhinitis or hay fever, asthma, eczema or atopic dermatitis, and food allergies. The risk of allergic disease is increased to about 1 in 3 if one first degree relative (parent or sibling) is atopic and to 70% if both parents are atopic [4]. The pattern of allergy expression differs with age, with the greatest incidence of food allergy and atopic eczema peaking by 1 year of age while asthma and allergic rhinitis continue to rise until around 15 years of age [5].…”
Section: Introductionmentioning
confidence: 97%
“…Influence of an allergic maternal environment on Adam33 mRNA and Adam33 protein expression in the lungs of offspring Maternal atopy is a strong risk factor for developing BHR and asthma 18,21,22 early in life. To investigate the impact of maternal allergy on Adam33 expression, we used A/J mice (Bhr1 locuspositive).…”
Section: Adam33 Expression In Hel Explant Cultures In the Presence Ofmentioning
confidence: 99%
“…1,8,9 However, a soluble form of ADAM33 (sADAM33) has been identified in bronchoalveolar lavage (BAL) fluid from subjects with asthma, where its levels are inversely correlated with lung function. 10 ADAM33/Adam33 is a member of the multifunctional ADAM family of Zn 21 -dependent metalloproteases. The protein is composed of the signal sequence, pro-, metalloprotease-, disintegrin-, cysteine-rich-, epidermal growth factor-like-, transmembrane-, and cytoplasmic domains, to which specific functions have been attributed.…”
mentioning
confidence: 99%